PHYSICAL ACTIVITY LEVELS, BODY MASS INDEX, MUSCULAR ENDURANCE, HAMSTRING FLEXIBILITY AND CARDIOVASCULAR ENDURANCE OF OLDER ADOLESCENTS IN KHYBER PAKHTUNKHWA PROVINCE, PAKISTAN - Muhammad Imran Khan; Muhammad Naseeb Ullah Khan; Aqeel Ahmad Khan (The Sky)
Abstract: Insufficient physical activity and Sedentary lifestyle is making youth susceptible to several chronic diseases globally and in Pakistan. This research assessed the association between levels of physical activity and health related fitness status of school and college students from different regions of Khyber Pakhtunkhwa.